Production of Biochar from Food Waste and its Application for Phenol Removal from Aqueous Solution - Lee, Chang Gu; Hong, Seung Hee; Hong, Seong Gu; Choi, Jae Woo; Park, Seong Jik (Water, Air, and Soil Pollution, 2019)
Deriving biochar from biowaste facilitates its reuse and application for environmental protection. This study addresses the adsorption of phenol onto food waste–based biochar (FWC). Phenol adsorption on FWC was affected by pyrolysis temperature, and the highest adsorption capacity was found at a temperature of 700 °C (FWC700). The characteristics of the biochar including morphology, surface area, functional groups, and elemental composition were analyzed. Additional batch experiments were performed to evaluate the phenol adsorption on FWC700 under various experimental conditions such as contact time, initial concentration, reaction temperature, solution pH, adsorbent dose, and presence of competing ions. The adsorption capacity of phenol decreased gradually from 9.79 ± 0.04 to 8.86 ± 0.06 mg/g between solution pH of 3 and 11. Copper sulfate showed the greatest interference on phenol adsorption to FWC in aqueous solution. Phenol removal at different contact times followed pseudo-second-order kinetics, and the Langmuir isotherm model provided the best fit of the equilibrium data with a maximum adsorption capacity of 14.61 ± 1.38 mg/g. Adsorption of phenol increased with increasing temperature from 15 to 35 °C, and thermodynamic analysis indicated an endothermic and spontaneous nature of the adsorption process. Biochar derived from food waste can be used as bio-adsorbent for the removal of phenol from aqueous solution.
Keywords: Bio chars; Experimental conditions; Food waste; Langmuir isotherm models; Phenol removal; Pseudo second order kinetics; Pyrolysis temperature; Thermo dynamic analysis; Adsorption; Biochar; Food waste; Phenol removal; Pyrolysis temperature